2011
DOI: 10.1038/aps.2010.220
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rh2 inhibits glioma cell proliferation by targeting microRNA-128

Abstract: Aim: To examine the influence of ginsenoside Rh2 (Rh2), a triterpene saponin extracted from the traditional medicinal plant ginseng, on the expression of miRNAs in human glioma cells. Methods: The expression profile of miRNA (miR) was analyzed in human U251, T98MG and A172 glioma cells using a miRNA array and quantitative real-time PCR. Cell viability was assessed using a colorimetric assay (cell counting kit-8). Transfection of miR-128 was performed using Lipofectamine 2000. Caspase 3 activity was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 33 publications
1
50
0
1
Order By: Relevance
“…In order to identify additional molecular pathways participating in the anticancer effect of Rh2, we performed miRNA expression profiling analysis with the aim to detect specific regulators of the Rh2-mediated anticancer properties in NSCLCs. On the basis of a recent report that Rh2 inhibits glioma cell proliferation by targeting miR-128, it is considered a novel mechanism for the anticancer effect of Rh2 (13). In the present study, we discovered that the expression of specific miRNAs in Rh2-treated A549 cells was significantly altered when compared to that in the untreated A549 (control) cells (Fig.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…In order to identify additional molecular pathways participating in the anticancer effect of Rh2, we performed miRNA expression profiling analysis with the aim to detect specific regulators of the Rh2-mediated anticancer properties in NSCLCs. On the basis of a recent report that Rh2 inhibits glioma cell proliferation by targeting miR-128, it is considered a novel mechanism for the anticancer effect of Rh2 (13). In the present study, we discovered that the expression of specific miRNAs in Rh2-treated A549 cells was significantly altered when compared to that in the untreated A549 (control) cells (Fig.…”
Section: Resultssupporting
confidence: 56%
“…Several health benefits of Rh2 have been reported due to its anti-inflammatory, antiGinsenoside Rh2 mediates changes in the microRNA expression profile of human non-small cell lung cancer A549 cells osteoclastogenic, anti-hyperglycemic and anticancer effects (10)(11)(12)(13)(14). The anticancer effect of Rh2 has been particularly observed in NSCLCs.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the clinic significance of PIs, accumulating clinical evidence indicates that the incorporation of HIV PIs into HAART is associated with various adverse effects, such as metabolic syndrome characterized by dyslipidemia, insulin resistance, and lipodystrophy [2,3] . 20(S)-Ginsenoside Rh2 (Rh2), a component isolated from red ginseng [4] , is one of the most studied ginsenosides due to its various pharmacological activities, such as anti-cancer effects, anti-hyperglycemic effects, and anti-obesity effects [5][6][7][8] . Rh2 has been approved as a complementary food by the China State Food and Drug Administration since 2006, and it can be speculated that Rh2 is popular among HIV-infected patients, especially in the individuals with AIDS and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Recently, researchers have found that 20(S)-GRh2 exhibits anticancer effects and could inhibit growth of several cancer cell lines and induce apoptosis in mammalian tumor cells. [14][15][16] However, the details of the signal transduction cascade involved in 20(S)-GRh2-induced death in Reh cells remaine unclear.…”
mentioning
confidence: 99%